2020
DOI: 10.1002/cssc.202001975
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Electrocatalytic Oxygen Evolution Efficiency through Cobalt‐Induced Intrastructural Enhancement and Electronic Structure Modulation

Abstract: Electrolytic water splitting using surplus electricity represents one of the most cost-effective and promising strategies for hydrogen production. The high overpotential of the oxygenevolution reaction (OER) caused by the multi-electron transfer process with a high chemical energy barrier, however, limits its competitiveness. Here, a highly active and stable OER electrocatalyst was designed through a cobalt-induced intrastructural enhancement strategy combined with suitable electronic structure modulation. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Over the past few years, many efforts have been made for the design and development of various advanced nonprecious metal-based electrocatalysts. Among them, nitrogen-doped carbon (NC) materials confined with transition metal nanoparticles are indentified to be the promising electrocatalysts toward OER, HER, or ORR processes because of their intrinsic advantages of excellent electrical conductivity, rich active sites, and high activities . Recently, zeolitic imidazole frameworks (ZIFs) have been repeatedly proven to be ideal precursors for the preparation of metal–N-C catalysts, in which the metal centers and ligands of ZIF materials can supply transition metals and carbon sources doped with heteroatoms, respectively. However, direct high-temperature carbonization strategy may result in a decrease in both nitrogen content and porosity of the prepared metal-embedded NC product, thereby greatly reducing the available active sites and limiting the mass transfer process, which will seriously affect the catalytic activity of the material .…”
mentioning
confidence: 99%
“…Over the past few years, many efforts have been made for the design and development of various advanced nonprecious metal-based electrocatalysts. Among them, nitrogen-doped carbon (NC) materials confined with transition metal nanoparticles are indentified to be the promising electrocatalysts toward OER, HER, or ORR processes because of their intrinsic advantages of excellent electrical conductivity, rich active sites, and high activities . Recently, zeolitic imidazole frameworks (ZIFs) have been repeatedly proven to be ideal precursors for the preparation of metal–N-C catalysts, in which the metal centers and ligands of ZIF materials can supply transition metals and carbon sources doped with heteroatoms, respectively. However, direct high-temperature carbonization strategy may result in a decrease in both nitrogen content and porosity of the prepared metal-embedded NC product, thereby greatly reducing the available active sites and limiting the mass transfer process, which will seriously affect the catalytic activity of the material .…”
mentioning
confidence: 99%
“…In addition, the ionic hydrogel has low vapor pressure, high chemical stability, thermal stability, and resistance to extreme environments. , For the bottom layer of the hydrogel, the adhesion will decrease when the human skin is sweating. Therefore, mussel-inspired hydrogel, which is composed of dopamine or 3,4-dihydroxyphenylalanine ( l -Dopa), can be a pioneer candidate to address the above issues, since marine mussels show a super capacity to adhere to various substrates (including organic and inorganic) under wet or dry environments. , The results of our previous work also demonstrated that mussel-inspired hydrogel exhibited 1.2 MPa adhesive strength under wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Currently, various advanced and low-cost non-precious metal-based electrocatalysts are being designed and developed. [17][18][19][20][21] Among these are nitrogen-doped carbon (NC) materials with transition metal nanoparticles as the main active sites. 22,23 Owing to the satisfactory inherent benefits of catalysts like outstanding conductivity of electrons, abundant active sites, and excellent activity, NC materials are considered promising electrocatalysts for OER or ORR processes.…”
Section: Introductionmentioning
confidence: 99%